(untitled) (Baghdad Science Journal, 2025)
Electrophoretic Deposition (EPD) process offers various advantages like the fabrication of the ceramic coatings and bodies with dense packing, good sinterability and homogenous microstructure. The variables namely (applied potential, deposition time and sintering temperature) affected the development of hydroxyapatite (HAP) coatings. The coating weight and thickness were found to increase with the increase in applied potential or coating time. Sintering temperature was found to affect in change phases of the metal, furthermore the firing shrinkage of the HAP coating on a constraining metal substrate leads to serve cracking. XRD Characterization indicates the formation of a contamination free phase pure, and the optical micrographs show the relatively uniform distribution of the HAP coatings. Analysis of the stiochiometric HAP before EPD process and after sintering indicates that the structural aspects do not change i.e. the EPD in ethanol does not affect the structure of HAP powder.